2007
DOI: 10.1515/znb-2007-0417
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase, Acetylcholinesterase Inhibitory and Antibacterial Activities of Chemical Constituents of Barleria prionitis

Abstract: Phytochemical studies on the ethanolic extract of Barleria prionitis of Sri Lankan origin have resulted in the isolation of a new compound, balarenone (1), along with three known compounds, pipataline (2), lupeol (3) and 13,14-seco-stigmasta-5,14-diene-3-α-ol (4). The structures of 1 -4 were elucidated with the aid of extensive NMR spectroscopic studies. Compounds 1 -4 showed moderate inhibitory activity against glutathione S-transferase (GST) and acetylcholinesterase (AChE). Compounds 1, 2 and 4 also exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…In cases where there were lower activities against Gram-negative bacteria, this could be due to the thick murein layer in their structure preventing the entry of inhibitors (Matu and Van Staden, 2003). Our findings agree with a report by Kosmulalage et al (2007) who observed antibacterial activity of ethanolic extract of aerial parts of B. prionitis against S. aureus and Pseudomonas aeruginosa. They reported the isolation of a new compound, balarenone along with other known natural products, pipataline and 13,14-seco-stigmasta-5,14-diene-3-␤-ol from the ethanolic extract, all of which showed antibacterial activity against Bacillus cereus and P. aeruginosa.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In cases where there were lower activities against Gram-negative bacteria, this could be due to the thick murein layer in their structure preventing the entry of inhibitors (Matu and Van Staden, 2003). Our findings agree with a report by Kosmulalage et al (2007) who observed antibacterial activity of ethanolic extract of aerial parts of B. prionitis against S. aureus and Pseudomonas aeruginosa. They reported the isolation of a new compound, balarenone along with other known natural products, pipataline and 13,14-seco-stigmasta-5,14-diene-3-␤-ol from the ethanolic extract, all of which showed antibacterial activity against Bacillus cereus and P. aeruginosa.…”
Section: Resultssupporting
confidence: 92%
“…Barleria prionitis L. is widely used in folk medicine to treat infection-related ailments (Kosmulalage et al, 2007). The leaves are reportedly used in fever, toothache, liver ailments, ulcers, piles treatment and irritation control; the aerial parts in inflammation and the roots to disperse boils and glandular swellings (Singh et al, 2003;Verma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these traditional medicinal uses, BP has been reported to possess anti-respiratory syncytial virus (Chen et al, 1998), antiarthritic, anti-inflammatory and hepatoprotective activities (Sing et al, 2003(Sing et al, , 2005, antihepatotoxic, antistress and immunorestorative (Suri et al, 2003), glutathione S-transferase, acetylcholinesterase inhibitory and antibacterial (Kosmulalage et al, 2007) activities. Previous work on the iridoid constituents (monoterpene lactone glucosides) of BP have led to the isolation and identification of shanzhiside methyl ester, 8-O-acetyl shanzhiside methyl ester (barlerin), 6,8-O,O-diacetyl shanzhiside methyl ester (acetylbarlerin) (Taneja and Tiwari, 1975;Damtoft et al, 1982;Byrne et al, 1987;Fathalla et al, 2009) and 6-O-trans-p-coumaryl-8-O-acetyl shanzhiside methyl ester and its cis isomer (Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(family: Acanthaceae) is an annual shrub, about 30-90 cm, found throughout the tropical regions of India, Sri Lanka, and South Africa. BP has been also reported to possess anti-stress and immunorestorative [6], glutathione S-transferase, and acetylcholinesterase inhibitory and antibacterial effects [7][8][9]. The plant is commonly used to treat whooping cough, fever, toothache, swellings, arthritis, gout, leprosy, and acts as an expectorant, diaphoretic and wound healer [1,2].…”
Section: Introductionmentioning
confidence: 99%